2021
DOI: 10.1038/s41598-021-96241-7
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular detection and genetic diversity of Leucocytozoon sabrazesi in chickens in Thailand

Abstract: Leucocytozoon sabrazesi is the intracellular protozoa of leucocytozoonosis, which is transmitted by the insect vectors and affects chickens in most subtropical and tropical regions of the globe, except South America, and causing enormous economic losses due to decreasing meat yield and egg production. In this study, L. sabrazesi gametocytes have been observed in the blood smears, and molecular methods have been used to analyse the occurrence and genetic diversity of L. sabrazesi in blood samples from 313 chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Haemosporidian infections in domestic hens and wild birds have been expanding in Thailand [ 39 , 40 , 41 , 42 ]. In the study by Pramual et al, [ 21 ] it was demonstrated that C. mahasarakhamense , C. guttifer , and C. huffi were infected with Leucocytozoon and two of P .…”
Section: Discussionmentioning
confidence: 99%
“…Haemosporidian infections in domestic hens and wild birds have been expanding in Thailand [ 39 , 40 , 41 , 42 ]. In the study by Pramual et al, [ 21 ] it was demonstrated that C. mahasarakhamense , C. guttifer , and C. huffi were infected with Leucocytozoon and two of P .…”
Section: Discussionmentioning
confidence: 99%
“…The slow progress in understanding the biology of leucocytozoids is unfortunate. Species of Leucocytozoon , the agents of avian leucocytozoonosis, are not only cosmopolitan, but, contrary to haemoproteids (Haemoproteidae) and malaria parasites (Plasmodiidae), they are actively transmitted in countries with not only warm climates [ 3 , 4 , 5 , 10 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], but cold climates [ 7 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and high mountains [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In other words, birds are under the threat of leucocytozoonosis nearly globally.…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies of genetic diversity of Leucocytozoon sp. based on the mitochondrial gene sequences in several countries, and almost all of these studies focused on the cytb gene [ 8 , 18 , 29 , 44 ]. However, there has been no information available regarding the genetic diversity and phylogeny of L. sabrazesi mitochondrial genes in Thailand until now.…”
Section: Discussionmentioning
confidence: 99%